2 - Acquiring Pedagogic Authority While Learning to Teach - McDonald, Zahraa; Sayed, Yusuf; De Kock, Tarryn; Hoffmann, Nimi (Africa Development, 2021)
are interconnected. Learning to teach and teach meaningfully and equitably is a core priority of education reforms. In this article we reflect on what the process of learning to teach might mean for teachers in an education system. We ask how and to what extent initial teacher education mitigates and reduces education inequities. In particular, we examine the relationship between teaching practice as a core component of initial teacher education and education inequities. The article draws on data examining the nature of student teachers’ experiences of teaching practice in the Western Cape of South Africa. We argue that the data illustrates that teaching practice does indeed invest future teachers with pedagogic authority. As such, it does indeed legitimate the position of student teachers in the classroom and within the education system, albeit with varying and differentiated outcomes for equity.